2020
DOI: 10.1007/s40475-020-00206-1
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy Transmission in Amazonian Countries: Current Status and Future Trends

Abstract: Purpose of Review Leprosy is one of the first pathologies described in the history of mankind. However, the ecology, transmission, and pathogenicity of the incriminated bacilli remain poorly understood. Despite effective treatment freely distributed worldwide since 1995, around 200,000 new cases continue to be detected yearly, mostly in the tropics. This review aims to discuss the unique characteristics of leprosy in Amazonian countries, which exhibit a very heterogeneous prevalence among human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 94 publications
0
10
0
3
Order By: Relevance
“…Eradication (rather than elimination) is almost certainly not feasible at any point in time for environmental and sylvatic mycobacteria. However, the mention of zoonotic transmission is a welcome addition to global Hansen's disease strategy, and we agree that research is needed, ideally directed from within endemic countries which have zoonotic reservoirs [32].…”
Section: Applying a One Health Approach To Public Health Policy In Brazilmentioning
confidence: 95%
See 1 more Smart Citation
“…Eradication (rather than elimination) is almost certainly not feasible at any point in time for environmental and sylvatic mycobacteria. However, the mention of zoonotic transmission is a welcome addition to global Hansen's disease strategy, and we agree that research is needed, ideally directed from within endemic countries which have zoonotic reservoirs [32].…”
Section: Applying a One Health Approach To Public Health Policy In Brazilmentioning
confidence: 95%
“…A better understanding of pathways to infection, including that these might not be from person to person, is also important in destigmatising disease. Brazil has not only ample scientific capacity to conduct such research and build the necessary evidence base [4], but is also well placed to collaborate with neighboring countries where zoonotic transmission presents a barrier to the elimination of Hansen's disease from endemic foci [32].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Numerous RT‐PCR reagents 15 necessary to probe the model for clues to leprosy pathogenesis have been developed as well. Armadillos naturally infected with M. leprae are found in the Gulf Coast area of the United States and in other parts of the Americas, 16,17 and their role as reservoir hosts for transmission of leprosy to humans has been documented 18‐20 …”
Section: Animal Models For Leprosymentioning
confidence: 99%
“…In 2009, Koba et al analyzed the trends and patterns of native leprosy in Japan [14]. However, in the countries of the Amazon region, not until 2020 when Schaub et al in [15] demonstrated the prevalence of distinct features of leprosy among humans and animal reservoirs. Kumar et al, in 2007, came out with a survey of leprosy disease among non-family contacts (NFC) and the family contacts (FC) of patients in Agra, India [16], while Fischer et al, in 2008, assessed the local distribution of leprosy cases in Bangladesh during 15-years of disease control program in Bangladesh [17].…”
Section: Introductionmentioning
confidence: 99%